Using a BSMV mediated genome editing system to validate the function of Fhb1 candidate genes in Fusarium head blight resistance - Kavetskyi, Volodymyr (Kansas State University, 2023)
Fusarium head blight (FHB) significantly reduces wheat grain yield and quality. It also produces mycotoxins within infected plant tissues that are harmful to human and animal. Using resistance genes in wheat cultivar is a most promising approach to prevent FHB epidemics. To date, more than 500 QTLs have been found to be associated with FHB resistance. Among them, Fhb1 shows the most stable major effect on FHB resistance in wheat and has been used as a major source of resistance in breeding programs worldwide. Recently Fhb1 has been cloned as a histidine rich calcium binding protein (TaHRC), but its resistance mechanisms remain to be determined. CRISPR/Cas9 genome editing has been widely used for gene function determination. However, delivery of gene editing complex is a challenging step for hexaploid wheat due to low transformation efficiency for most wheat genotypes. In this study, we attempt to use our newly developed genome editing protocol for wheat to create Fhb1 mutations and evaluate their functions on wheat FHB resistance. We used previously developed Cas9-overexpressed Bobwhite that was generated by transformation as the Cas9 donor. We crossed the Cas9-overexpressed Bobwhite plants to Ning 7840 and selected their F₂ plants with both Cas9 and the target genes for gene editing. Barley stripe mosaic virus (BSMV) was used to deliver guide RNA (gRNA) to selected Cas9-carrying wheat plants. Treated plants were screened for mutations by sequencing target fragments in an ABI 3730 sequencer. Plants with mutations were evaluated for FHB responses in greenhouse conditions. We identified three mutants with two carrying frame shift mutations (mut_36, mut_99) and one carrying a nucleotide substitution (mut_123) in TaHRC. Sequence alignment with reference genome indicated that two mutants (mut_36 and mut_99) carried TaHRC mutations in A subgenome, and one (mut_123) had a TaHRC mutation in D subgenome. Phenotyping the mutants demonstrated no change in FHB susceptibility compared non-edited control plants. Our results indicated that BMSV mediated gene editing system does not require tissue culture step and can be used for delivery gRNA to hexaploid wheat. TaHRC homologs in A and D genomes did not affect FHB resistance.
Keywords: Fhb1; CRIPR; Gene-editing; Wheat